Water Supply in Kharkiv - Гарбуз, А. Г. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2017)
Purpose.  On the basis of the survey population to determine the priority of water supply sources for the big city. To monitor the quality of drinking water of the central water supply and natural sources of the city of Kharkiv. Methods. Questionnaires, physical and chemical methods. Results. According to the results of the population survey found that 53% of respondents used for drinking spring water from tanker trucks, 30% of respondents prefer water sources that are close to their place of residence. The water from the city water supply system for drinking purposes only use 15% of the respondents, and 2% from other water supply systems. Monitoring of the quality of drinking water of the central water and spring water. For tap water set the deviation from existing standards for five of the twenty examined indicators, indicating the poor quality of water. The study of spring water samples has identified it as a "clean". Conclusions. Spring water in Kharkov advised the public as an alternative source of drinking water.